Is HIV testing in antenatal clinics worthwhile? Can we afford it? - Chrystie IL; Zander L; Tilzey A; Wolfe CD; Kenney A; Banatvala JE (AIDS Care)
Since 0.2-0.4% of pregnant women attending antenatal clinics (ANC) at St Thomas's Hospital are HIV positive, and as the Department of Health (DH) have recommended that universal voluntary HIV testing be made available to women attending ANC in areas of 'known or suspected higher prevalence of HIV infection', we examined the implications of the DH initiative in an Inner London Teaching Hospital as well as in a General Practice involved in shared care. The cost of the programme (148,300 pounds to 193,900 pounds), 80% of which relates to the need to obtain informed consent, was approximately 2.7-3.5 times that calculated by the DH. The DH based much of their costing on additional time for counselling rather than calculating the additional staff required. We estimated that 25% of women will require specialized counselling since 17% are of African ethnicity and others are injecting drug users or 'worried well'. Various means of reducing costs were considered but, until such time as explicit, informed consent is no longer considered necessary, the above resources will be required. Unless the DH continues to provide central direction to Providing Agencies to give priority to these recommendations and, where necessary, provides additional funding, we fear that this important public health initiative will be unsuccessful.